Etnoecologia do Peixe-Boi da Amazônia (Trichechus inunguis) na província petrolífera de Urucu, Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The Amazonian manatee (Trichechus inunguis) is an aquatic mammal, pertaining to Sirenia Order and Trichechidae family. It resides at the biggest tributaries of the Amazonian basin, it’s the only order’s specie that lives exclusively in fresh water. In the past the specie suffered an intense commercial exploration, mainly between 1930 to 1950 decades. In this period is esteemed around 200 thousand animals had been killed. Nowadays the specie has been listed as an animal “vulnerable to the extinction” by IUCN. In the region of Urucu River (Coari city-AM), characteristic area of occurrence and utilization by the specie, a scientific research, was developed between the years of 2006 and 2007, targeting to characterize limnology and to study the habitants traditional knowledge in the areas of Urucu River and in the lakes of Urucu, Aruã, Coari and Coari Grande. To the limnologic characterization the collect of the physical-chemicals parameters was realized: water temperature, depth, transparency, watercourse speed, pH, electric conductive and dissolved oxygen, with three copies to each area, to each hydrologic cycle time (low water, dryness, high water and over flowing). The results are compatible with the others Solimões River dark waters affluent. The Urucu river, even been characterized as a dark water river, shows low transparency and an inclination to white water coloration. The offer of aquatic plants as supplies to the Amazonian Manatee alternates a lot because of the differences between the water levels in the hydrologic time of over flowing and dryness. The dryness and the low water periods are with lower supplies available. Although the productions beginner at large areas of pasture in the region lakes that would serve as supplies to the Amazonian Manatee during all the high water and over flowing periods is watched. The ships traffic in the study area showed a higher intensity around Coari city and around the gas-tube buildings. To obtain the information about the traditional knowledge from the regions habitants about the Amazonian Manatee was realized interviews semistructured that made 74 inhabitants pertaining to 33 communities. To a better quality of data, these interviews were directed to the eldest inhabitants, to the Amazonian Manatee fishermen and to the communities leaders. Between those asked, 14 inhabitants assumed to have already fished at least one Amazonian Manatee at the studied zone. Between the years of 2004 to 2007 were registered a total of 17 abated animals. The harpoon is the equipment used to fish the Amazonian Manatee, but the “malhadeiras” (a kind of Amazonian fishing net) shows risk to accidental captures, mainly for species nestling. Half of the local inhabitants believe that the density of Amazonian Manatee has suffered reduction in the studied zone, mainly because of the fact that is still happening Amazonian Manatee captures. According the inhabitants, the Amazonian Manatee can be almost totally used to consume, taking off just the bones and the hardest leathers parts. The meat trade of Amazonian manatee, even forbidden by law, it is still occurring in the area. About the alimentary habits, the asked mentioned 29 species of aquatic and semi-aquatics plants consumed by Amazonian Manatee. The asked inhabitants showed extensive knowledge about biology, reproduction, alimentary habits and Amazonian Manatee distribution. These informations are considered importants instruments for future conservation works of the specie.
Keywords: Trichechus inunguis (Peixe-Boi); Peixe-boi - Conservação; Peixe-boi - Etnoconhecimento; CIÊNCIAS AGRÁRIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA